THE GIBBS FREE ENERGY OF FORMATION AND HEAT CAPACITY OF β-RH2O3 AND MGRH2O4, THE MGO-RH-O PHASE DIAGRAM, AND CONSTRAINTS ON THE STABILITY OF MG2RH4+O4 - Nell J.; O'Neill H.S.C. (My University, 1997)
The oxygen potentials of the reactions 43Rh + O2 = 23β-Rh2O3 and 23MgO + 43Rh + O2 = 23MgRh3+2O4 were measured using electrochemical cells of the type Pt, metal + oxide #CSZ#YDT (air), Pt. Relative to a reference pressure of 1 bar we find μO2(B-Rh2O3) (+/-63 J . mol-1) = -278500 + 283.8T - 11.69T ln T (860 K < T < 1355 K) and μO2(MgRh2O4) (+/-110 J . mol-1) = -297314 + 369.405T - 23.3338T ln T (940 K < T < 1495 K). The constant pressure heat capacities of β-Rh2O3 and MgRh2O4 were measured with a differential scanning calorimeter operated in step heating mode between 360 K and 1065 K. Best fits to the data (in J . mol-1 . K-1 with an uncertainty of +/-2 J . mol-1 . K-1) give Cp(β-Rh2O3) = 123.6 + 0.0141T - 208.8T-0.5 - 2312000T-2 and Cp(MgRh2O4) = 174.0 + 0.014T - 4297000T-2A third law analysis showed satisfactory internal consistency of the Gibbs free energy of formation and heat capacity data of β-Rh2O3, but with a much lower value for S298.15,β-Rh2O3 (71.5 +/- 1.5 J . mol-1 . K-1 compared with 106.27 J . mol-1 . K-1; Barin, 1989). This is attributed to the new Cp(β-Rh2O3) data that are significantly different from the original measurements of Wohler and Jochum (1933) and the adjusted values of Barin (1989).Spinels prepared in the MgO-Rh-O system are solid solutions between MgRh3+2O4 and Mg2Rh4+O4 and the interpretation of the data for μO2(MgRh2O4) requires an understanding of phase relationships in the MgO-Rh-O system. From an isothermal projection of oxygen potentials onto the Mg-Rh binary at 1373 K, the mol fraction MgRh3+2O4 in spinel (XMgRh2O4) in equilibrium with MgO and Rh at 1373 K was estimated to be about 0.92. (i.e., XMg2RhO4 # 0.08). This provides a calibration point for determining the temperature dependence of aspinelMgRh2O4 in MgRh3+2O4-Mg2Rh4+O4 solid solutions.